USING THE INTERNET IN HIGH SCHOOL MATHEMATICS - Loong, Esther Yook-Kin (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
Whilst the technological, pedagogical and content knowledge (TPACK) model has beenÃ‚Â increasingly adopted for understanding teachersÃ¢â‚¬â„¢ use of technology, there have been many callsÃ‚Â for greater discussion about the constituent constructs, their relationship with one another andÃ‚Â the central TPACK. This paper analyses qualitatively the TPACK demonstrated by the teacherÃ‚Â of a Year 11class who used web-based simulated contexts and interactive web objects in aÃ‚Â Mathematics Studies course. The findings indicate aspects of TPK relating to academicÃ‚Â learning time and the transformational mode of the technology were not fully realised in thisÃ‚Â case study. The implications these has for teacher professional development are discussed.Keywords: Classroom Teaching, Interactive Learning Environments, TPACK, MathematicsÃ‚Â Education, Pedagogical Issues.Ã‚Â DOI: http://dx.doi.org/10.22342/jme.5.2.1496.108-126